2016
DOI: 10.17507/tpls.0603.10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Input-based and Output-based Instruction on EFL Learners' Autonomy in Writing

Abstract: Abstract-The current research investigates the comparative effects of input-based and output-based taskinduced activities on EFL learners' autonomy in writing. 35 learners were homogenized out of 70 Preintermediate EFL learners. The methodology was that at first session, a task of writing -similar to the writing tasks in their book-was given to all the participants in both experimental groups of input-based and outputbased. During six treatment sessions some vocabularies related to the writing task is taught t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
0
8
1
Order By: Relevance
“…The results revealed that the group receiving explicit method of teaching collocations outperformed the other two groups in using collocations in sentence writing. Salimi and Shams (2016) investigated the comparative effects of input-based and output-based task induced activities on EFL learners' autonomy in writing. 35 learners were homogenized out of 70 Pre-intermediate EFL learners.…”
Section: Input-based Vs Production-based Instructionmentioning
confidence: 99%
“…The results revealed that the group receiving explicit method of teaching collocations outperformed the other two groups in using collocations in sentence writing. Salimi and Shams (2016) investigated the comparative effects of input-based and output-based task induced activities on EFL learners' autonomy in writing. 35 learners were homogenized out of 70 Pre-intermediate EFL learners.…”
Section: Input-based Vs Production-based Instructionmentioning
confidence: 99%
“…This finding corroborates Swain's (2000) Output Hypothesis, based on which output tasks, due to their challenging nature, evoke EFL learners to process information more deeply. A number of previous studies lend support to this finding (Alavinia & Rahimi, 2019;Salimi & Shams, 2016;Vosoughi & Mehdipour, 2013;Webb, 2005). For instance, Alavinia and Rahimi (2019) and Vosoughi and Mehdipour (2013) concluded that students using productive tasks learn substantially more vocabulary compared to those using receptive tasks.…”
Section: Discussionmentioning
confidence: 75%
“…The importance of input or output tasks has been brought into light in a set of empirical studies (Alavinia & Rahimi, 2019;Hashemi Shahraki & Kassaian, 2011;Roohani, Forootanfar & Hashemian, 2017;Salimi & Shams, 2016;Vosoughi & Mehdipour, 2013;Webb, 2005). For example, Webb (2005) probed the effects of glossed sentences (as input tasks) and sentence creation (as an output task) on Japanese learners' word knowledge.…”
Section: The Role Of Tasksmentioning
confidence: 99%
“…In line with these studies, Salimi and Shams (2016) also investigated the comparative effects of input and output focused activities on L2 learners' autonomy in writing in English. There were 18 pre-intermediate female participants in each group.…”
Section: Is 'Only' Comprehensible Input Sufficient For Language 'Acquisition'?mentioning
confidence: 99%